Utility of serum lysosomal enzyme assay in the detection of cerebral sphingolipidoses in patients with progressive neurologic dysfunction - Christopher, Rita (Springer India, 1997)
The cerebral sphingolipidoses which form part of a larger group of lysosomal disorders can be detected and conclusively confirmed by the demonstration of the relevent enzyme deficiency in easily available tissue samples like serum. We have assayed acid β-galactosidase, β-hexosaminidase and its isozymes hexosaminidase A and B, and arylsulfatase A in the serum of patients with progressive cerebral dysfunction and detected 18 patients with enzyme defects, thereby confirming the diagnosis of a specific type of cerebral lipidosis in these patients. The assay of serum lysosomal enzymes was of immense diagnostic use as it obviated the need for highly invasive techniques like a brain biopsy.